Development and Application Rasch Model to The Measurement of Tazkiyatun Nafs Instrument for Madarasah Teachers - Rijal Firdaos; Dina Indriana; Siti Shalihah; Aspandi; Beya Soltani (Universitas Pesantren Kh abdul Chalim Mojokerto, 2026)
Good character is an essential factor for a teacher in transferring knowledge to students, alongside mastery of methods and subject matter. The lack of a standardized instrument for assessing the Tazkiyatun Nafs dimension among Madrasah teachers constitutes the primary research problem addressed in this study. This study aimed to develop and validate the Tazkiyatun Nafs instrument for Madrasah teachers using Rasch model analysis. The study population consisted of 405 Madrasah teachers, including 230 female and 175 male teachers. The data collection method used a 1–5 Likert-scale survey. The results of the Rasch analysis, conducted with the Winsteps program, indicated that 13 of 16 items on the Tazkiyatun Nafs instrument met the item-fit criteria and were distributed across four dimensions. The unidimensionality results showed that the Tazkiyatun Nafs instrument measures only a single construct; empirical results indicate that the proportion of variance explained by the measurement exceeds 30%. Item-fit statistics confirm a high level of conformity with the Rasch Model, as reflected by mean-square (MNSQ) values within the acceptable interval of 0.5 < MNSQ < 1.5. Reliability indicators also exhibit strong internal consistency, with item reliability reaching 0.99 and Cronbach’s Alpha recorded at 0.81. The findings of this study indicate a substantive alignment between the theoretical framework and the empirical evidence. The developed measurement model demonstrates coherence with the underlying conceptual structure, thereby offering policymakers practical utility for evaluating teachers’ competencies in the affective domain. Likewise, its reliability value demonstrated a high consistency index. Overall, it can be concluded that the Tazkiyatun Nafs instrument for Madrasah teachers has good psychometric properties and can be used for research and assessment purposes, particularly for evaluating affective characteristics among Madrasah teachers.